The Carotenoid Diatoxanthin Modulates Inflammatory and Angiogenesis Pathways In Vitro in Prostate Cancer Cells - Clementina Sansone; Luigi Pistelli; Luana Calabrone; Angelo Del Mondo; Angelo Fontana; Marco Festa; Douglas M. Noonan; Adriana Albini; Christophe Brunet (MDPI AG, 2023)
Xanthophylls, a group of carotenoids, have attracted attention as human health benefit compounds thanks to their functionality and bioavailability. The great antioxidant and anti-inflammatory abilities of diatoxanthin (Dt), a photoprotective xanthophyll synthetized by diatoms, were recently documented. This study investigates the capacity of Dt to intercept prostate cancer progression in vitro on different human cell lines, exploring its role against cancer proliferation and angiogenesis. Our results highlighted the chemopreventive role of Dt already at low concentration (44.1 pM) and suggest that the Dt-induced cancer cell death occurred through oxidative stress mechanisms. This hypothesis was supported by variations on the expression of key genes and proteins. Oxidative stress cell deaths (e.g., ferroptosis) are recently described types of cell death that are closely related to the pathophysiological processes of many diseases, such as tumors. Nonetheless, the interest of Dt was further strengthened by its ability to inhibit angiogenesis. The results are discussed considering the actual progress and requirements in cancer therapy, notably for prostate cancer.